THE RELATIONSHIP BETWEEN FAMILY SUPPORTS TOWARDS THE EARLY COMPLEMENTARYFEEDING FOR 0-6 MONTHS BABIES IN PUBLIC HEALTH CENTER, SEWON I BANTUL, INDONESIA - Tiasna, Apriani; Astutik, Dhesi Ari (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Early Complementary Feeding (ECF) is a critical period in which the babyâs digestive system is not perfect yet. If an inappropriate food is being given, the food wonât be digested well and will cause digestive problems. The high intensity of complementary food is one of the causes occurs by family support. Research Purpose: The research purpose was to identify the correlation between family support and complementary food feeding in 0-6 months babies in Public Health Center, Sewon I Bantul, Indonesia. Research Method: The researchers usedanalytical survey method with Cross Sectional time approach. The subjects of the research were mothers who have 7-12 months babies with 34 respondents and used Non-Probability Sampling with total sampling technique. The data were analyzed using Chi Square correlation test. Research Result: The results were obtained from 34 respondents, who provide early complementary feeding with 21 respondents (61,76%), and the majority of women who have a high level of support that provide early complementary feeding with 10 respondents (8,6%). Conclusion: The research showed that there is a correlation between early complementary food feeding and family support with the significance value p value = 0.012 (Î± < 0.05). Information sharing with family about the importance of motherâs support especially in feeding the breast milk is very essential so that mothers could give a good and adequate nutrition for their babies.Â